Maternal and Neonatal Risk Factors Associated with Positive Toxicology Results - Pee, Hannah; Hussein, Karen; Del Savio, Gina; Kocherlakota, Prabhakar (American Journal of Perinatology, 2025)
The incidence of substance use disorder (SUD) during pregnancy continues to increase; however, the identification of SUD is challenging. The significance of individual risk factors and their association with toxicology is contentious. To identify maternal and neonatal risk factors associated with positive toxicology results for nonprescribed substance use during pregnancy.This retrospective study included pregnant persons and their infants, who were screened for predetermined risk factors for SUD during pregnancy. The toxicology test results of pregnant persons' urine and infants' urine, meconium/umbilical cord were correlated with risk factors.Maternal risk factors (history of prepregnancy or current SUD, on medication for opioid use disorders, insufficient prenatal care, sexually transmitted and blood-borne infections) and neonatal risk factors (neonatal opioid withdrawal syndrome, intrauterine growth restriction) showed a correlation with toxicology results.Combining maternal and neonatal risk factors with toxicology testing may accurately identify SUD in pregnancy.
Keywords: neonatal opioid withdrawal; drug use; pregnancy; neonatology; drug testing; prenatal drug testing; indications for drug testing; drug toxicology